Studies on High Frequency Shoot Regeneration in Sesame (Sesamum indicum L.) - Wadeyar, Bangaramma S.; Lokesha, R. (Plant Tissue Culture and Biotechnology, 2012)
High frequency shoot regeneration was attempted in sesame (Sesamum indicum L. Pedaliaceae), using five genotypes/varieties viz. Tumkur and Gulbarga Locals (land races), W-II, E-8 and DS-1 (varieties). The hypocotyl-derived callus obtained through direct seeding method was placed on MS with five different treatments viz. pre-culture of callus on high sucrose (6 - 9%) for two weeks and transferring on to plain MS with 3% sucrose, MS with variable concentrations of TDZ alone, MS with constant TDZ and variable concentrations of BA and IAA, MS with variable concentrations of BA and IAA without TDZ, MS with ABA and AgNO3 and MS with BAP, NAA and AgNO3. Highest frequency of cent per cent shoot regeneration was initiated in variety DS-1on MS containing NAA 2.5 mg/l, BAP 3.5 mg/l and 20 µM AgNO3 with 2.50 mean shoots/callus followed by 91.6% in variety W-II on MS containing 25 µM TDZ with 2.20 mean shoots/callus. The other treatments had poor shoot regeneration response. The results have been discussed in the light of sesame improvement through biotechnological ways. Key words: Sesamum indicum, hypocotyl, high frequency, shoot regeneration D. O. I. 10.3329/ptcb.v21i1.9562 Plant Tissue Cult. & Biotech. 21(1): 45-52, 2011 (June)